-3(4n+6)=-6(n-8)

Simple and best practice solution for -3(4n+6)=-6(n-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4n+6)=-6(n-8) equation:


Simplifying
-3(4n + 6) = -6(n + -8)

Reorder the terms:
-3(6 + 4n) = -6(n + -8)
(6 * -3 + 4n * -3) = -6(n + -8)
(-18 + -12n) = -6(n + -8)

Reorder the terms:
-18 + -12n = -6(-8 + n)
-18 + -12n = (-8 * -6 + n * -6)
-18 + -12n = (48 + -6n)

Solving
-18 + -12n = 48 + -6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '6n' to each side of the equation.
-18 + -12n + 6n = 48 + -6n + 6n

Combine like terms: -12n + 6n = -6n
-18 + -6n = 48 + -6n + 6n

Combine like terms: -6n + 6n = 0
-18 + -6n = 48 + 0
-18 + -6n = 48

Add '18' to each side of the equation.
-18 + 18 + -6n = 48 + 18

Combine like terms: -18 + 18 = 0
0 + -6n = 48 + 18
-6n = 48 + 18

Combine like terms: 48 + 18 = 66
-6n = 66

Divide each side by '-6'.
n = -11

Simplifying
n = -11

See similar equations:

| .03x+.05(200-x)=9 | | 7m-25=-4 | | 2m+20=26 | | X^2-8x-4=-11 | | 3.3=1.5-0.4 | | x+4k=0 | | -18=x-5 | | -15x+25=-95 | | 9z-17=-35 | | 10y-2=48 | | -11y-9=-86 | | -15p-1=-46 | | 31-3n=4(n+6) | | C+32=-8 | | (5x^3+1)-1=0 | | 3822/14 | | 60.00+42.95p=25.00+49.95p | | -4y-13=15 | | 10x-11=-1 | | -2(n-5)=3n(n-6) | | -13x+15=-63 | | x-.20x=366 | | x-.20x=390 | | 8p-3=77 | | x-20x=390 | | 6(1-4v)=3(4-7v) | | -8x+8x-21=-12-16 | | -y+20=12 | | 99=11m | | 7p+3=-53 | | 2x+5-3=3 | | 15N-25=-100 |

Equations solver categories